HUBUNGAN TINGKAT PENGETAHUAN LANSIA TENTANG VAKSIN COVID-19 DENGAN TINGKAT KECEMASAN LANSIA DALAM MENGIKUTI VAKSINASI COVID-19 - puspita, ayu (AHM Center, 2023)
Introduction: In the elderly, there is still a lot of knowledge about the covid-19 vaccine that does not know what the benefits and objectives of vaccination are, causing the elderly to worry about the safety and effectiveness of the covid-19 vaccine. Vaccination can have a direct impact on the elderly. The impact is emotional and physical. Emotionally (psychologically) one of the responses the emerges is anxiaty. Objective: This study aims to see the relationship between the level of knowledge of the elderly about the covid-19 vaccine with the level of anxiety of the elderly in participating in the covid-19 vaccination. Methods: Correlation descriptive research design with cross sectional approach. A sample of 88 respondents, sampling using purposive sampling technique. The analysis used univariate analysis to see the frequency distribution of respondents characteristics, a description of the elderly’s knowledge about tha covid-19 vaccine and a description of the elderly’s anxiety in participating in the covid-19 vaccination, as well as bivariate analysis using the pearson product moment correlation test. Result: The result of this study showed that respondents with good knowledge of the covid-19 vaccine are 27 people (30,7%) and respondents with sufficients knowledge of the covid-19 vaccine are 61 people (69,3%). Meanwhile, on the anxiety level variable, it was found that 54 people (61,4%) who experienced mild anxiety about the covid-19 vaccination, 34 people (38,6%) who experienced moderate anxiety about the covid-19 vaccination.. The result of the statistical test obtained P value 0,029< (0,05). Conclusion: The result of statistical tests show that there is a relationship between the knowledge of the elderly about the covid-19 vaccine and the anxiety of the elderly in participating in the covid-19 vaccination.